War and oncology: cancer care in five Iraqi provinces impacted by the ISIL conflict - Skelton, Mac; Al-Mash'hadani, Ahmed Khalid; Abdul-Sater, Zahi; Saleem, Mohammed; Alsaad, Saad; Kahtan, Marwa; Al-Samarai, Ahmed Hazim; Al-Bakir, Ahmed Moyed; Mula-Hussain, Layth (Frontiers in Oncology, 2023)
War and cancer have been intertwined in Iraq for over three decades, a country where the legacies and ongoing impacts of conflict have been commonly associated with both increased cancer rates as well as the deterioration of cancer care. Most recently, the Islamic State of Iraq and the Levant (ISIL) violently occupied large portions of the country’s central and northern provinces between 2014 and 2017, causing devastating impacts on public cancer centers across central and northern Iraq. Focusing on the five Iraqi provinces previously under full or partial ISIL occupation, this article examines the immediate and long-term impacts of war on cancer care across three periods (before, during, and after the ISIL conflict). As there is little published data on oncology in these local contexts, the paper relies primarily upon the qualitative interviews and lived experience of oncologists serving in the five provinces studied. A political economy lens is applied to interpret the results, particularly the data related to progress in oncology reconstruction. It is argued that conflict generates immediate and long-term shifts in political and economic conditions that, in turn, shape the rebuilding of oncology infrastructure. The documentation of the destruction and reconstruction of local oncology systems is intended to benefit the next generation of cancer care practitioners in the Middle East and other conflict-affected regions areas in their efforts to adapt to conflict and rebuild from the legacies of war.